2022
DOI: 10.3389/fcimb.2022.968422
|View full text |Cite|
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor contributes to immunopathogenesis during Plasmodium yoelii 17XL infection

Abstract: Macrophage migration inhibitory factor (MIF) is a cytokine recognized regulator of the inflammatory immune response associated with several immune cells that produce inflammatory cytokines such as IL-1β, IL-6, IL-12, IL-18, and TNF-α. This study aimed to understand the effect of MIF on the immune response and pathogenesis during Plasmodium infection. Wild-type (Wt) and MIF knockout (Mif-/-) mice were intravenously infected with 1×103Plasmodium yoelii (Py) 17XL-parasitized red blood cells. Our data showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 86 publications
0
0
1
Order By: Relevance
“…An opposite trend was observed in a study on Plasmodium yoelii infections [90]. In this research, MIF-deficient mice showed lower parasitemia and delayed host mortality.…”
Section: Parasitic Infectionscontrasting
confidence: 70%
“…An opposite trend was observed in a study on Plasmodium yoelii infections [90]. In this research, MIF-deficient mice showed lower parasitemia and delayed host mortality.…”
Section: Parasitic Infectionscontrasting
confidence: 70%